Utilization of Artificial Intelligence (AI) Perplexity as a Digital Literacy Tool for Islamic Religious Education Students - Rahmawati, Sufiyah; Inayati, Nurul Latifatul (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
Technology, particularly artificial intelligence (AI), is rapidly advancing and transforming nearly all aspects of life, including education. In the context of Islamic Religious Education, technology can strengthen understanding of religious teachings as well as shape students' character and moral values. Digital literacy is becoming increasingly important, especially for IRE students, not just the ability to use technological devices, but also the critical capacity to understand and evaluate digital information. One way to enhance digital literacy in IRE is by utilizing AI technologies, such as Perplexity AI, which can assist students in accessing, analyzing, and interpreting religious information accurately and critically. Surveys show that 43% of students are already using AI. This study aims to explore how AI can improve digital literacy for IRE students at the University of Muhammadiyah Surakarta. This research uses a phenomenological approach with a qualitative method to analyze the impact of AI in IRE learning. The findings indicate that AI, particularly Perplexity, accelerates the search for literature and provides broader access to information. However, there are challenges related to dependence on technology, which could weaken students' non-digital literacy skills. Despite this, the potential of AI in enriching the digital literacy of IRE students is significant.